Pomen komuniciranja z bolnikom oziroma varovancem ob sprejemu v splošno ambulanto - Makari, Zdenka (Obzornik zdravstvene nege, 1999)
The author present the interaction between patient/client and nursing technician upon admission to health center, as well as the significance of communication upon the first contact. Standards for admission of a patient/client to a health center is explained. The application of the resultsin practice can be very useful.
Keywords: Ambulatory care; bolniki; Communication; health care; komuniciranje; medsebojni odnosi; Nurse-patient relations; Nursing care; Standards; zdravstvo